Optimalisasi Akupresur sebagai Terapi Nonfarmakologis untuk Meningkatkan Perfusi Otak dan Meredakan Nyeri Kepala - Nuraenah, Nuraenah; Saryono, Saryono (Universitas Malahayati, 2025)
ABSTRACT Headaches are one of the most common medical complaints in the world, affecting the quality of life and productivity of individuals. One of the main causes of headaches is impaired brain tissue perfusion. Non-pharmacological interventions, such as acupressure, are becoming increasingly popular, but there are still few studies explaining the underlying physiological mechanisms. to evaluate the effectiveness of acupressure in improving tissue perfusion and reducing headaches, as well as to identify the underlying physiological mechanisms and relevant acupressure points in headache treatment. This study uses a literature review approach with the PRISMA protocol. Data were collected from electronic databases such as PubMed, Google Scholar, and ScienceDirect with a publication range of 2019–2024. The selected articles include experimental studies, clinical trials, and literature reviews related to acupressure and brain tissue perfusion. Nine articles that met the inclusion criteria showed that acupressure at specific points, such as Tai Yang, He Gu (LI4), and Feng Chi (GB20), effectively increases brain tissue perfusion. The mechanism of acupressure involves the release of nitric oxide as a vasodilator, stimulation of the autonomic nervous system, and the release of endorphins. The research results also noted a reduction in pain intensity, headache frequency, and an increase in cerebral blood flow. Acupressure is an effective and cost-efficient non-pharmacological intervention for alleviating headaches and enhancing cerebral tissue perfusion. This intervention has great potential to be integrated into modern nursing practice and healthcare services. Keywords: Acupressure, Brain Perfusion, Headache, Acupressure Points, Migraine. ABSTRAK Nyeri kepala merupakan salah satu keluhan medis paling umum di dunia, yang memengaruhi kualitas hidup dan produktivitas individu. Salah satu penyebab utama nyeri kepala adalah gangguan perfusi jaringan otak. Intervensi nonfarmakologis, seperti akupresur, semakin diminati namun belum banyak kajian yang menjelaskan mekanisme fisiologis yang mendasarinya. Untuk mengevaluasi efektivitas akupresur dalam meningkatkan perfusi jaringan dan mengurangi nyeri kepala, serta mengidentifikasi mekanisme fisiologis dan titik akupresur yang relevan dalam pengobatan sakit kepala. Penelitian ini menggunakan pendekatan tinjauan literatur dengan protokol PRISMA. Data dikumpulkan dari basis data elektronik seperti PubMed, Google Scholar, dan ScienceDirect dengan rentang publikasi 2019–2024. Artikel yang dipilih mencakup studi eksperimental, uji klinis, dan tinjauan literatur terkait akupresur dan perfusi jaringan otak. Sembilan artikel yang memenuhi kriteria inklusi menunjukkan bahwa akupresur pada titik tertentu, seperti Tai Yang, He Gu (LI4), dan Feng Chi (GB20), efektif meningkatkan perfusi jaringan otak. Mekanisme akupresur melibatkan pelepasan oksida nitrat sebagai vasodilator, stimulasi sistem saraf otonom, dan pelepasan endorfin. Hasil penelitian juga mencatat pengurangan intensitas nyeri, frekuensi sakit kepala, serta peningkatan aliran darah serebral. Akupresur merupakan intervensi nonfarmakologis yang efektif dan hemat biaya untuk mengatasi nyeri kepala serta meningkatkan perfusi jaringan otak. Intervensi ini memiliki potensi besar untuk diintegrasikan ke dalam praktik keperawatan dan layanan kesehatan modern. Kata Kunci: Akupresur, Perfusi Otak, Nyeri Kepala, Titik Akupresur, Migrain